2018
DOI: 10.14238/sp19.5.2018.284-9
|View full text |Cite
|
Sign up to set email alerts
|

Perbandingan Prediktor Mortalitas Skor PRISM III dan PELOD 2 pada Anak Sakit Kritis Non Bedah

Abstract: Latar belakang. Tujuan utama perawatan pasien di PICU adalah untuk menyelamatkan jiwa pasien yang mengalami sakit kritis, tetapi masih dapat disembuhkan. Sarana, prasarana, sumber daya manusia yang terbatas di PICU dengan biaya rawat yang mahal masih menjadi perhatian utama. Sistem skoring digunakan untuk memprediksi luaran dan prognosis pasien. Sampai saat ini, belum ada sistem skoring yang digunakan di PICU secara baku untuk penilaian awal pasien di Indonesia. Tujuan. Menganalisis perbandingan kemampuan pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In addition, study in Indonesia used a PELOD-2 cut-off value of ≥20, and found that such patients had a 7.75 times greater risk of death. 21 The SOFA, a system for evaluating organ dysfunction, was recommended by the most recent consensus. 6,19 Pediatric SOFA is SOFA with adjustments.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, study in Indonesia used a PELOD-2 cut-off value of ≥20, and found that such patients had a 7.75 times greater risk of death. 21 The SOFA, a system for evaluating organ dysfunction, was recommended by the most recent consensus. 6,19 Pediatric SOFA is SOFA with adjustments.…”
Section: Discussionmentioning
confidence: 99%
“…The PRISM score can assess the severity of a patient's disease by using its 17 components (Pollack et al, 2015). A study by Bramantyo et al at revealed that critically ill children who had a PRISM score of > 8 had a mortality rate of 3.5 folds greater than critically ill children who had a PRISM score of < 8 (Bramantyo et al, 2018).…”
mentioning
confidence: 99%